2005
DOI: 10.1890/03-5400
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Expert Opinion in Ecological Models Using Bayesian Methods: Impact of Grazing on Birds

Abstract: Abstract. One of our greatest challenges as researchers is predicting impacts of land use on biota, and predicting the impact of livestock grazing on birds is no exception. Insufficient data and poor survey design often yield results that are not statistically significant or that are difficult to interpret because researchers cannot disentangle the effects of grazing from other disturbances. This has resulted in few publications on the impact of grazing on birds alone.Ecologists with extensive experience in bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
176
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(192 citation statements)
references
References 74 publications
5
176
0
2
Order By: Relevance
“…Ecologists have used Bayesian priors and metaanalyses to combine information from different sources (Downing et al 1999, Hedges et al 1999, Ellison 2004, McCarthy 2007 Martin et al 2005). In this study, informative priors provided support for our estimates through similarities between estimates of relative survival with and without the use of prior information, and similarities between the prior information and estimates of apparent annual survival.…”
Section: Informative Priorsmentioning
confidence: 61%
See 1 more Smart Citation
“…Ecologists have used Bayesian priors and metaanalyses to combine information from different sources (Downing et al 1999, Hedges et al 1999, Ellison 2004, McCarthy 2007 Martin et al 2005). In this study, informative priors provided support for our estimates through similarities between estimates of relative survival with and without the use of prior information, and similarities between the prior information and estimates of apparent annual survival.…”
Section: Informative Priorsmentioning
confidence: 61%
“…A number of ecological studies have improved the precision of model estimates by including Bayesian informative priors (e.g., Martin et al 2005, McCarthy and Masters 2005, McCarthy et al 2008). In our study, there was a small but noticeable improvement in precision for estimates of apparent annual survival rates when some prior information was included compared with using vague priors, but there was little or no improvement in the precision of the relative apparent survival rate when informative priors were used.…”
Section: Informative Priorsmentioning
confidence: 99%
“…Examination of the frequencies of counts of animal observations demonstrated that the data included more zeros than can be expected from either a Poisson or a negative binomial distribution. A high frequency of zeros can arise in several ways (Kuhnert et al 2005, Martin et al 2005a). Structural zeros result from an ecological effect; for example, a strong seasonal or environmental gradient causes some sites to have no animals present in one season or under particular conditions (e.g., heavy hunting).…”
Section: Zip Models To Model Animal Guild Densitiesmentioning
confidence: 99%
“…Rapid assessment projects draw on distributed expertise to gather the best existing knowledge about an emerging issue when decisions need to be made before scientific consensus is reached (Howarth et al 2009). Further, key stakeholders' perspectives on emerging issues have been used in a variety of settings to guide decisions of importance (Government Accountability Office 2008;Goodman 2007;Martin et al 2005). This study's key stakeholders included scientists and farmers.…”
mentioning
confidence: 99%